Quenching a rotary hollow cylinder by multiple configurations of water-impinging jets. (July 2019) - Jahedi, Mohammad; Moshfegh, Bahram
Highlights: Transient quenching experiment was carried out by multiple water-impinging jets. Hydrodynamic phenomena of quenching by multiple jets was discussed. Effectiveness of quenching parameters was analyzed on local average heat flux. Characteristic of maximum heat flux at stagnation and upwash point was studied. Effect of the quenching parameters was studied on average heat transfer. Abstract: Experiments have been conducted to analyze quenching of a hot rotary hollow cylinder by one and two rows of water-impinging jets. Sub-cooled water jets ( Δ T sub = 45 –85 K) with flow rate 8006 to 36, 738 impinged on hollow cylinder with rotation speed 10 to 70 rpm at various initial wall superheat temperatures from 250 to 600 ° C . Jet-to-jet and jet-to-surface spacing varied between 4 to 10 d and 1.5 to 7 d respectively and angular position of impinging jets were tested from 0 to 135 ° . Effectiveness of the defined parameters on stagnation point's local average heat flux was found lower in the film and nucleate boiling compare to transition boiling regime where rotation speed had the highest impact. Characteristic of maximum heat flux ( MHF ) at stagnation point and upwash flow point were analyzed based on surface heat flux, time and temperature corresponding to MHF . Same maximum heat flux levels were captured in the both points which reveals importance of the flow behavior at the upwash flow point. The effectiveness of the parameters to improve average heat transfer was studied based on cooling area of each water-impinging jet in the multiple configurations. Higher average heat transfer was obtained by increasing flow rate and subcooling temperature and lower initial wall superheat temperature corresponding to onset of transition boiling regime.